ANALISIS FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI KEPUTUSAN IBU TIDAK MEMBERIKAN ASI EKSKLUSIF - Utami, Utami; Yulita, Hendra; Noorma, Nilam; Rofiqoh, Rofiqoh; Anwar, Seniwaty (Ensiklopedia of Journal, 2024)
Based on an initial survey, the number of mothers who do not provide exclusive breastfeeding increases every year, so there are various factors that influence the lack of optimality in exclusive breastfeeding. The purpose of the study was to determine the relationship between socioeconomic factors that influence mothers' decisions not to provide exclusive breastfeeding. This type of research uses quantitative with a cross sectional approach. The research was conducted in June 2022 using consecutive sampling. The sample amounted to 109 people. The results showed that there was a relationship between education level (p value: 0.006), working status (p value: 0.001) on exclusive breastfeeding. It is recommended for health workers, especially those who provide treatment to mothers and children, it is hoped that the results of this study can be used as discussion or reference material related to improving the performance of health services in a place or area of coverage of their work area. Keywords: Exclusive breastfeeding, work, education